Maize crop nutrient input requirements for food security in sub-Saharan Africa - Berge, Hein F.M. ten; Hijbeek, Renske; Loon, Marloes P. van; Rurinda, Jairos; Tesfaye, Kinde; Zingore, Shamie; Craufurd, Peter Q.; Heerwaarden, Joost van; Brentrup, Frank; Schröder, Jaap J.; Boogaard, Hendrik L.; Groot, Hugo L.E. de; et al. (Elsevier, 2019)
Nutrient limitation is a major constraint in crop production in sub-Saharan Africa (SSA). Here, we propose a generic and simple equilibrium model to estimate minimum input requirements of nitrogen, phosphorus and potassium for target yields in cereal crops under highly efficient management. The model was combined with Global Yield Gap Atlas data to explore minimum input requirements for self-sufficiency in 2050 for maize in nine countries in SSA. We estimate that yields have to increase from the current ca. 20% of water-limited yield potential to approximately 50–75% of the potential depending on the scenario investigated. Minimum nutrient input requirements must rise disproportionately more, with N input increasing 9-fold or 15-fold, because current production largely relies on soil nutrient mining, which cannot be sustained into the future.